Australia's oral history collections a national directory. - National Library of Australia (Canberra : National Library of Australia, 1999)
Based on the printed publication of the same name (published in 1997) the database allows you to search for oral history recordings held within over 400 Australian institutions and private collections. These collections document Australian life, customs, politics and traditions and cover a wide range of subjects.
Title from title screen (viewed on 31 August 2001).
Text.
Mode of access: Internet via World Wide Web. Available at: https://webarchive.nla.gov.au/awa/20000611233225/http://www.nla.gov.au/apps/ohdir
Keywords: Folklore libraries -- Australia -- Directories; Oral history -- Library resources -- Directories; Oral history -- Archival resources -- Directories; Folklore archives -- Australia -- Directories; Australia -- Biography -- Archival resources -- Directories; Australia -- Biography -- Library resources -- Directories